Oppression and Identity in Bradbury’s Fahrenheit 451 - Aulia Ikhsanti (Passage, 2015)
This study explores the oppression and identity in Ray Bradbury’s Fahrenheit 451 (henceforth, F451). It examines the portrayal of oppression in the F451 society and how these oppressions affect the main protagonist’s identity construction. To meet the purposes, the study was designed under cultural materialism approach and applies Young’s theory on oppression known as Five Faces of Oppression (1990) and Hall’s theory on identity as the theoretical framework of the study. The findings reveal that there are five forms of oppression evident in the novel: exploitation, marginalization, powerlessness, cultural imperialism, and violence. It also indicates that the main protagonist’s identity is constructed by the oppression that he observes and notices through his interaction with characters and things around him. As the result of these oppressions, Montag’s identity is transformed from ignorant to non-conformist. Seeing from the cultural materialism perspective, the fictional world of F451 is a metaphor of a more media-absorbed society of America 1950s. As such, this oppression should be resisted. In this case, Montag’s identity construction can be interpreted as the representation of the resistance. Thus, parallel to its context, F451 presages the threat of media dominance and at the same time offers a possible way to fight against it.Keywords: Oppression, Identity, Cultural Materialism, Fahrenheit 451